2014
DOI: 10.1097/ccm.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

ICU Architectural Design Affects the Delirium Prevalence

Abstract: Critically ill patients admitted in single-bed rooms have a lower prevalence of delirium than those admitted in multibed rooms. However, coma/delirium-free days, first day in delirium, and motoric subtypes were not different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…All but one have used CAM-ICU and RASS for delirium detection and subtyping, respectively. HD prevalence rates were broadly ranged (36–100%) and the development of HD was associated with adverse short-term outcome in most studies [ 38 43 ]. Neurologic conditions were associated with HD in two studies [ 39 , 44 ].…”
Section: Hypoactive Delirium In Different Wardsmentioning
confidence: 99%
“…All but one have used CAM-ICU and RASS for delirium detection and subtyping, respectively. HD prevalence rates were broadly ranged (36–100%) and the development of HD was associated with adverse short-term outcome in most studies [ 38 43 ]. Neurologic conditions were associated with HD in two studies [ 39 , 44 ].…”
Section: Hypoactive Delirium In Different Wardsmentioning
confidence: 99%
“…The deprivation of exposure to natural light and exposure to artificial light have been related to changes in the circadian rhythm, sleep disorders, and delirium . ( 3 , 12 ) However, Khon et al found no effect of the presence of windows and exposure to sunlight on outcomes in critically ill patients. ( 13 ) Measures such as exposure to natural light, maintenance of the circadian rhythm, and minimization of artificial light exposure at night are part of a bundle for promoting sleep, with satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described how sleep deprivation can trigger episodes of delirium in ICU patients. 26 55 Admittance to individual rooms, 62 and the application of protocols targeted towards eliminating sleep disruptors are effective interventions for avoiding delirium. 55 The role of nursing staff is fundamental, as some of the activities (changing bed linen, manipulation of venous catheters, the administration of medications, taking vital signs) are great sleep disruptors.…”
Section: Discussionmentioning
confidence: 99%